PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN RETENSI SISWA DALAM PEMBELAJARAN IPA KELAS V SDN 130 PEKANBARU - Hendri Marhadi; Syahrilfuddin Syahrilfuddin; Liyaumi Liyaumi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2013)
The research aim to examine effect of model cotextual teaching and learning(CTL) for improved student’s retention in sience learning. Contextual teachingand learning (CTL) was a concept which help the teacher to make world and thelearning was connected. The CTL was identically with presented real things in theclassroom. Instead retention were a memory of information who can be rememberafter ths students do the learning. One group pre-test-post-test design were usedto analyze data. 12 weeks after posttest the retest were do for analyze thestudent’s retention. The result proved the Model Cotextual Teaching AndLearning (CTL) were significantly influenced the student’s retention in siencelearning at fifth class SDN 130 Pekanbaru City. Mean of student’s retention inthis research is up to 130 % with ’very good’ cretheria. Furthermore, thecotextual teaching and learning (CTL) was identified dominantly influence thestudent’s memory or retention.Keyword: contextual teaching and learning (CTL), student’s retention, siencelearning.